#### Answer

2x-y = 6

#### Work Step by Step

(3;0), (7;8)
m=$\frac{8-0}{7-3}$=$\frac{8}{4}$=2
slope 2 , through (3;0)
y-$y_{1}$=m(x-$x_{1}$)
y-0=2(x-3)
0=2x-6-y
6=2x-y

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

2x-y = 6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.